The association between admission serum albumin and preoperative deep venous thrombosis in geriatrics hip fracture: a retrospective study of 1819 patients with age ≥ 65 years - Yi-Lun Wu; Dan Zhang; Kai-Yuan Zhang; Ting Yan; Wen-Si Qiang; Ting Zhang; Bin-Fei Zhang (BMC Musculoskeletal Disorders, 2023)
Abstract Objective This study evaluated the association between serum albumin levels and preoperative deep vein thrombosis (DVT) in geriatric hip fractures. Methods Older adult patients with hip fractures were screened between January 2015 and September 2019. The demographic and clinical characteristics of the patients were collected. Multivariate binary logistic regression and generalized additive model were used to identify the linear and nonlinear association between albumin levels and preoperative DVT. Analyses were performed using EmpowerStats and the R software. Results A total of 1819 patients were included in this study. The average age was 79.37 ± 6.88 years. There were 550 males and 1269 females. The preoperative albumin was 38.19 ± 4.07 g/L. There were 580 (31.89%) preoperative DVTs. Multivariate binary logistic regression showed that albumin level was associated with preoperative DVT (odds ratio [OR] = 0.94, 95% confidence interval [CI]: 0.91–0.97, P = 0.0002) after adjusting for confounding factors. The fully adjusted model showed a DVT risk decrease of 6% when albumin concentration increased by one g/L after controlling for confounding factors. In addition, the trend test and propensity score matching also showed a stable linear correlation between albumin level and preoperative DVT. Conclusion Serum albumin is associated with preoperative DVT in geriatric patients with hip fractures, and it could be considered a predictor for the risk of DVT. Registration ID ChiCTR2200057323.